Mechanical properties of high strength POM-FRCC and its performance under elevated temperatures. (5th July 2021) - He, Jianqiang; Wang, Qing; Yao, Boyu; Ho, Johnny
Highlights: POM-FRCC with ductile performance is developed. POM fibres improve the spalling resistance of cementitious composite. Hair-line cracks propagate with the increase of temperature beyond 400 °C. Additional hydrates found around 200–400 °C contribute to strength increase. POM fibres shrink beyond 200 °C resulting in pore coarsening. Abstract: Polyoxymethylene (POM) is one of the polymers with excellent mechanical and durable properties developed in recent years. It has attracted much attention in construction materials thanks to its great concordant compatibility with cement paste in the form of fibre. To evaluate the influence of POM fibres on high strength mortar, compressive, flexural and uni-axial tensile performance of POM fibre-reinforced cementitious composite (POM-FRCC) were experimentally tested in the present study. Results show that 2.0 vol% POM fibres significantly increased the ductility of high strength mortar. Moreover, behaviors of elevated temperatures exposed POM-FRCC were focused in consideration of thermal sensitive nature in polymer fibre. Results indicate that POM fibres help to effectively prevent the spalling of high strength mortar due to their melting around 280 °C. Additional hydration products were detected at 200–400 °C through XRD curves, which might be responsible for the enhancement of compressive strength. Hair-line cracking can be observed under SEM observation beyond 400 °C and propagates as the increase of the heating temperature. POM fibres were found shrunk at 200 °C and disappeared after 400 °C heating, leaving longitudinal channels in the composite. The mechanical properties of composites are greatly reduced beyond 600 °C thanks to the synthetic effects of pore coarsening effect, crack propagation and hydrates decomposition.